Fundamentals of mathematics and statistics paper - I, XI Arts and science Rev.syllabus - Deshpande Rekha, Saptarshi R., Desai N. sargar G.K. (Nirali Prakashan, Pune, 2006)
Stats/Maths
ENGLISH
Keywords: Fundamentals of mathematics and statistics paper - I, XI Arts and science Rev.syllabus; Stats/Maths; Stats/Maths